Educational Support: Phenomenological Study Among Industry Focal Person on their Corporate Social Responsibility to Labas Senior High School - Maronilla, Ma. Virginia B.; Deada, Lani D.; Pendon III, Fernando T. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the lived experiences and challenges faced by industry focal persons in implementing Corporate Social Responsibility (CSR) initiatives to support education at Labas Senior High School. Employing a phenomenological research design, the study aimed to understand how CSR is experienced, delivered, and sustained within the educational context through in-depth interviews. Findings revealed that industry partners perceive CSR as a values-driven, community-based partnership fostering both educational development and organizational growth. Participants highlighted the importance of authentic, inclusive engagement to achieve meaningful impact. CSR initiatives supported academic enrichment, resource provision, and collaborative learning opportunities for students and faculty. However, challenges emerged, including difficulties aligning CSR activities with organizational and educational goals, internal constraints such as limited manpower and shifting priorities, and the necessity of strategic leadership to sustain CSR commitments. The study underscores the vital role of responsive problem-solving and leadership involvement in enhancing CSR outcomes. Furthermore, it emphasizes continuous collaboration between industry partners and educational institutions to promote sustainable and impactful CSR practices. These insights provide valuable guidance for current and prospective industry partners aiming to strengthen their educational support through CSR.